Estrogen-related seizure exacerbation following hormone therapy for assisted reproduction in women with epilepsy. (October 2018) - Mostacci, Barbara; Esposto, Roberta; Lello, Stefano; Bisulli, Francesca; Licchetta, Laura; Tinuper, Paolo
Abstract: Purpose: Exogenous estrogens might lead to seizure worsening in women with epilepsy (WWE) by lowering the seizure threshold and inducing glucuronidation in women taking lamotrigine. Assisted reproduction techniques are increasingly used and often require estrogenic and estrogen raising hormone therapy. We aimed at reporting their possible impact on seizures in WWE. Methods: We describe two cases of seizure exacerbation following hormone therapy for assisted reproduction in WWE. Results: Patient 1: 46 years old woman, with right temporal dysplasia. At 40 years she had monthly focal seizures, possibly progressing to bilateral tonic-clonic seizures, she took levetiracetam 3000/day and she underwent gonadotropin therapy for ovarian stimulation. Estrogen blood levels showed a sudden and significant rise, up to 1019 pg/ml and she had a concomitant cluster of three tonic-clonic seizures in 24 h. Patient 2: 41 years old woman with focal epilepsy of unknown etiology. At 38 years she was taking lamotrigine 450 mg/day and had been seizure free for three years. She took estradiol valerate 4 mg for 10 days for endometrial preparation for embryo transfer and had the only seizure over six years, with the exception of auras during advanced pregnancy, related to marked decrease of lamotrigine blood levels. During adjunctive concomitant therapy with clobazam, neither patient had seizures while on hormone therapy. Conclusions: Our data suggest that hormone therapy for assisted reproduction could exacerbate seizures and should be carefully monitored in WWE, especially those taking drugs inactivated by glucuronidation. Adjunctive concomitant antiepileptic therapy should be considered.